IMPACT OF TRAFFIC INCIDENT ON A NETWORK WIDE LEVEL - Rompis, Semuel Y. R. (JURNAL SIPIL STATIK, 2018)
Incident is apparently known as a source of traffic congestion. A number of ITS strategies have been implemented to minimize this problem however most of them were evaluated in microscopic level. This study utilizes a real world condition to model the incident in a freeway. Several scenarios were setup to recognize the impact of the incident to the system in the congested network wide. The scenarios were differed from one to the other by vary the number of lane closure and also the incident duration. Impact of multi incident is also examined in this study. The result of this study is expected to be a component account for assessing a proper ITS strategy to be implemented in an area.Key words: Incident, traffic congestion, ITS strategy, microscopic level, Impact